Financial Risk Assessment Using Enterprise Risk Management Concept - Anastasia Filiana Ismawati (JOURNAL OF ACCOUNTING, ENTREPRENEURSHIP AND FINANCIAL TECHNOLOGY (JAEF), 2019)
Risk management by using risk mapping can help X Hospital located in Yogyakarta in financial management towards operating as an objective company. Enterprise Risk Management (ERM) helps organizations manage all the risks precisely and in a more integrated way. This research focuses on the risk assessment in X hospital that has not applied ERM, to analyse its financial risks. From this test, X Hospital is expected to manage its risks by using the ERM methods more, in order than the sustainability of the business can be maintained over a longer period, and thus, being able to compete with the competitors. Based on the results of risk the assessment, out of the 15 risks identified. There are top three risks that cannot be acceptable. They are: financial management report risk, contribution risk and multiple jobs risk of X Hospital. The three risks need to get response and allocations of good funds and attention from the management.